1983
DOI: 10.1002/bjs.1800700311
|View full text |Cite
|
Sign up to set email alerts
|

The use of graduated compression stockings in the prevention of postoperative deep vein thrombosis

Abstract: The efficacy of graduated compression stockings in the prevention of postoperative deep vein thrombosis was studied in a randomized, prospective, controlled trial of 200 patients, aged 40 years and over, undergoing abdominal surgery (100 for benign disease, 100 for malignant conditions). Deep vein thrombosis was diagnosed by the 125I-fibrinogen test. The incidence of deep vein thrombosis was 35.9 per cent in the control group (103 patients) and 15.5 per cent in the stockinged group (97 patients) (P less than 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
5

Year Published

1984
1984
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(44 citation statements)
references
References 20 publications
0
39
0
5
Order By: Relevance
“…20 Increased hematocrit has been the only predictive factor of venous and arterial thrombosis in subjects with polycythemia vera, whereas high platelet counts and abnormal platelet function were not significantly linked to polycythemia vera-associated thrombosis. 9,11,12 Rheological therapies, including compression devices 21 and hemodilution with dextran, 22 have been shown to reduce the risk of deep vein thrombosis in patients with polycythemia vera.…”
Section: Discussionmentioning
confidence: 99%
“…20 Increased hematocrit has been the only predictive factor of venous and arterial thrombosis in subjects with polycythemia vera, whereas high platelet counts and abnormal platelet function were not significantly linked to polycythemia vera-associated thrombosis. 9,11,12 Rheological therapies, including compression devices 21 and hemodilution with dextran, 22 have been shown to reduce the risk of deep vein thrombosis in patients with polycythemia vera.…”
Section: Discussionmentioning
confidence: 99%
“…A postal survey of orthopaedic surgeons in the UK showed that 68% used graded compression stockings as prophylaxis for DVT (Laverick, Croal and Mollan 1991). Their efficacy has been well documented in abdominal surgery (Holford 1976;Scurr et al 1977;Allan et al 1983;Turner, Cole and Brooks 1984;Wille-Jorgensen et al 1985;Jeffery and Nicolaides 1990), but there is little information on their use in orthopaedic surgery (Barnes et al 1978;Ishak and Morley 1981;Ohlund, Fransson and Starck 1983).…”
Section: Graded Compression Stockings For Prevention Of Deep-vein Thrmentioning
confidence: 99%
“…This modal ity has been demonstrated to be effective in low risk surgery. 21 The combination of the References Prophylaxis of deep vein thrombosis 561 above modalities is designed to reduce stasis, one of the major arms of Virchow's Triad. Low dose heparin (5,000 U, SC, 012 hrs) was chosen for its effect on redu cing hypercoagulability, another arm of Virchow's Triad.…”
Section: Discussionmentioning
confidence: 99%